Foto-Voz: Una herramienta visual para profundizar en las percepciones del campo y la agroecología - Espinosa, Nicola; Tristan, Maria Claudia; Urbani, Ilaria (2024)
This publication explores Photo-Voice, a participatory methodology where participants use photography to express their perceptions. A 2023 workshop in Curimaná engaged youth to reflect on agroecology through themes like the ideal farm and daily life. The method fostered dialogue, empowerment, and critical insights despite logistical and ethical challenges.